Female Functional Constipation Is Associated with Overactive Bladder Symptoms and Urinary Incontinence. (28th February 2017) - Maeda, Takahiro; Tomita, Masuomi; Nakazawa, Atsushi; Sakai, Gen; Funakoshi, Shinsuke; Komatsuda, Akari; Ito, Yujiro; Nagata, Hirohiko; Tsukada, Nobuhiro; Nakamura, So
Abstract : This noninterventional cross-sectional study aims to assess the association between functional constipation (FC) and urinary symptoms in female patients with no treatment for urination and defecation. The Rome III criteria for evaluation of defecation, Overactive Bladder Symptom Score (OABSS) for evaluation of urinary symptoms, and clinical features were investigated in 145 female patients. Latent FC and moderate to severe overactive bladder (OAB) were defined on the basis of positivity for two or more of the Rome III criteria and an OABSS ≥ 6 with OABSS Q3 ≥ 2, respectively. In 60 latent FC patients, the OABSS was higher (5.0 versus 3.2, p = 0.001 ), and concurrent moderate to severe OAB symptoms and OAB with urinary incontinence were more frequent than those in 85 nonlatent FC patients (33.3 versus 10.6%, p = 0.001, and 31.7 versus 7.1%, p < 0.001 ). Multivariate analysis demonstrated that moderate to severe OAB symptoms were a significant associated factor of latent FC (odds ratio (OR) = 4.125, p = 0.005 ), while latent FC was the only associated factor of moderate to severe OAB and OAB with urinary incontinence (OR = 4.227, p = 0.005 and OR = 4.753, p = 0.004 ). In conclusion, moderate to severe OAB symptoms are correlated with FC. Moreover, FC is related to moderate to severe OAB symptoms and to OAB with urinary incontinence.